JOYFULL LEARNING: MENINGKATKAN MOTIVASI BELAJAR SISWA PASRAMAN MELALUI MODEL PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF - Wisnu Wardani, Dewi Ayu (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2024)
Learning motivation is important for students to improve the quality of education. Technology can be used to make the learning environment more interesting and interactive. The purpose of this study is to determine how effective technology-based learning is in increasing students' desire to learn at school. To achieve this goal, this study uses a literature study method that collects data from a number of articles that have been published on the subject.By using media, applications, and e-learning, students can be more motivated to learn. Therefore, schools must pay attention to the use of technology in learning to increase students' motivation to learn. The solution offered in this study is an interactive learning media with the Joyful Learning method. The Joyful Learning method is a very good method used to involve students in learning the material that has been delivered considering that students are less active in the learning process. The results of the media expert validation in the visual communication category and ease of use are in the very valid category, with a percentage of the feasibility of 92%, while for the ease of use aspect 86%. Based on the calculation of validity by the material validator, the percentage of assessment for material suitability is 82%, material presentation is 80%, and material coverage is 92%. So the media summary for all aspects of evaluation by the material validator is very valid. Then the validation of the user value was obtained in the form of 86% of the content of the learning material, 82% of learning, and 84% of the display of learning media, with a valid category. The results of the analysis show that the use of technology-based learning methods can make students more motivated to learn.